(untitled) (Heritage, 2024)
This scholarly inquiry undertakes an examination of the enduring discourse surrounding technological determinism and its profound influence on the trajectory of cultural change. Within this multifaceted discourse, the study places a central emphasis on the transformative potential of emerging technologies, particularly artificial intelligence (AI), and their implications for cultural evolution and the preservation of human identity. Furthermore, this analysis extends its purview to consider the ethical dimensions inherent in the deployment of AI and the critical role played by cultural diversity in the ethical assessment of these technologies. Drawing on seminal works within the field, the discussion grapples with the conceptualization of technological determinism, echoing the insights of scholars such as Winner and McLuhan. While proponents of technological determinism posit that emerging technologies, such as AI, act as agents of cultural transformation, their perspectives are juxtaposed against those who perceive a perilous erosion of cultural diversity. In this context, the study critically engages with Winner’s "Autonomous Technology" to elucidate the socio-political ramifications of technological determinism, underscoring the need for a balanced ethical assessment. Ethical considerations applied to AI occupy a prominent place in this discourse. Cognizant of the transformative power of AI, scholars such as Bostrom and Floridi have probed into the ethical dimensions of AI deployment. The study reflects on their findings, highlighting the imperative of ethical vigilance in the development and application of AI technologies. It contends that ethical assessments of AI must be inherently bound to the preservation and enhancement of cultural diversity, thereby ensuring the equitable distribution of AI’s benefits. This analysis further delves into the existing digital divide and its intricate interplay with the ethical evaluation of AI. It acknowledges the sobering reality that unequal access to technology exacerbates social disparities. As articulated by DiMaggio and Hargittai, the digital divide reinforces existing inequities, underscoring the ethical imperative of addressing access disparities in the deployment of AI. In conclusion, this study advances a nuanced understanding of technological determinism’s role in cultural evolution and the pivotal importance of cultural diversity in the ethical evaluation of AI. It underscores the ethical duty to mitigate disparities in access to technology, thereby ensuring a more equitable and culturally diverse future in the age of AI.